Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content:1. The Role of University Environment and Student Activities in Promoting Citizenship Values among Students of the University of Nizwa as Perceived by Its Students and Staff: A Field Study during the 2010–2011 Academic SemesterMs. Aisha Khalfan Al -Waheibi2. Institutional Communication in the Digital Age: Innovative Strategies for Deepening Public Engagement through the Synergy of Knowledge Management and InnovationDr. Mohamed Ouldhali3. Scientific Research Methodology in Exploratory Qualitative Studies:  Methods, Approaches, and ToolsDr. El-Yazidi Reda4. The Quality of University Services and Its Relationship to Academic Efficiency: A Study on a Sample of Female Students in the Social Work Department at Umm Al-Qura University in MakkahDr. Rawan Ibrahim Alnasser5. The role of international intervention in defeating terrorism: (the sahel region as a case study)Ms. Mayssaa Nawaf Abdul-khalek6. Obstacles to the Arab knowledge industry from the perspective of researchers at King Khalid UniversityMs. Norah Ali Al-Shahri, Dr. Haya Mohammed Al-Shahri7. Study of the spatial suitability of commercial pharmacies in Hail city using geographic information systems (GIS)Ms. Asalah Maza Alshurayhi
Keywords: Journal of Human and Social Sciences